2008
DOI: 10.4012/dmj.27.702
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and solubility of luting cements in different solutions

Abstract: This study examined the solubility, sorption, and dimensional change of eight luting cements in two different solutions: 50% ethanol:water and distilled water. Ten disk specimens were prepared of each material following the manufacturers ' instructions, and then ground with silicone carbide paper. Sorption and solubility were calculated by weighing the specimens before and after immersion and desiccation. Data were analyzed by two-way ANOVA, Tukey ' s HSD and Fisher ' s PLSD tests. GC Fuji Plus and RelyX Lutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
4
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 32 publications
(48 reference statements)
8
77
4
7
Order By: Relevance
“…These values ranged from 0.89% to 7.32% among the different experimental groups. In a previous study 4) , in which the water sorption and solubility of a variety of commercial cements were evaluated, a similar fluid kinetics behavior was noted when the specimens were subjected to the same environment. Despite the differences in the methodology, water sorption and solubility results were found to be dependent on filler parameters such as type, size, content, and concentration.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…These values ranged from 0.89% to 7.32% among the different experimental groups. In a previous study 4) , in which the water sorption and solubility of a variety of commercial cements were evaluated, a similar fluid kinetics behavior was noted when the specimens were subjected to the same environment. Despite the differences in the methodology, water sorption and solubility results were found to be dependent on filler parameters such as type, size, content, and concentration.…”
Section: Discussionmentioning
confidence: 53%
“…A lower organic matrix content also helps to explain the lowest water uptake. Lower water sorption in high filler-loaded resins has previously been reported in the literature 4,35) . A highly filler-loaded composite may be more susceptible to disintegration once the matrix has degraded and a stable structure is no longer provided for the filler particles 26) .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…20 Braden and Clarke and Mese et al reported that filler volume is also related to water sorption, which means that resins contains higher filler volumes absorb less water. 21,22 If an adhesive monomer has a polarity and a solubility which are similar to those of a polymer substrate, the monomer may act as a solvent for the polymer and may infiltrate it. If both parameters are sufficiently different, the monomer and polymer are immiscible.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many discussions in the literature address the degradation 1 , color-change 2,3 , and leaching of monomers after simulated aging in various solvents, including saliva, water, and ethanol 4,5 . Water absorption was previously deemed beneficial to filling materials, as the consequent swelling was believed to compensate for polymerization shrinkage 6 .…”
Section: Introductionmentioning
confidence: 99%